KNOWLEDGE OF TEENAGERS AND PERSONAL HYGIENE BEHAVIOR IN SMP 036 KOTA BATAM - Ronny Sutanto; Isramilda Isramilda (Universitas Batam, 2021)
Background : One of the problems that must be considered by young women is their reproductive health. It is very important to inform young women about the menstrual process knowledge so that they will be able to maintain personal hygiene. Lack of knowledge about personal hygiene can increase the risk of infection. This study aims to determine the relationship between knowledge of young girls and personal hygiene behavior. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at SMPN 036 Batam City, the study was conducted for 6 months, the population in this study were all 270 students of SMPN 036 class VIII, with a total sample of 162, the sampling technique was carried out by purposive sampling technique with research instruments using a questionnaire. Data analysis using Chi square. Result :The results of the study were obtained from 162 respondents, the majority of respondents had good knowledge of 110 people (68%), and good personal hygiene behavior as many as 152 people (94%). Chi-square statistical test obtained p-value = 0.008 <0.05, conclusion : that there is a significant relationship between the knowledge of uterine adolescents with personal hygiene behavior at SMPN 036 Batam City. Advice for teenagers to maintain personal hygiene behavior.